Identifikasi Peran Guru dalam Rangka Optimalisasi Pengelolaan Pembelajaran Matematika di SMPK 2 Harapan - Putu Christin Mellyani; Kadek Rihendra Dantes; Basilius Redan Werang (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to identify the role of teachers in optimizing the management of mathematics learning at SMPK 2 Harapan Untal-untal Dalung, Bali. This type of research is descriptive qualitative research with the type of field research or field research. Data collection is done by interviews. Data analysis techniques are by reducing data, presenting data, and drawing research conclusions. The results showed that the role of teachers in optimizing the management of mathematics learning at SMPK 2 Harapan has been carried out well, namely by carrying out the role of teachers as demonstrators, namely by demonstrating good examples during the learning process to students in the classroom, as class managers, namely by paying attention to the environment and classroom climate so that the learning process runs well, as facilitators, namely by facilitating students in the process Learning, as an evaluator, namely by evaluating student learning outcomes and student attitudes when participating in classroom learning and as a motivator, namely by being a motivator for students so that students are encouraged into positive things during classroom learning. Factors that influence success in learning management are a) supporting factors which include the role of teachers, teacher discipline, facilities / infrastructure. b) inhibiting factors, which include student conditions, and learning methods.